Unusual location of recurrent mantle cell lymphoma on fluorodeoxyglucose-positron emission tomography despite complete metabolic resolution of previous sites of disease - Froitzheim, Benjamin; Boktor, Raef; Lau, Eddie; Lee, Sze (World Journal of Nuclear Medicine, 2020)
This case report presents a patient with recurrent pleomorphic mantle cell lymphoma (MCL), which is a relatively rare but aggressive type of lymphoma. A positron emission tomography/computed tomography scan performed to assess treatment response demonstrated a complete metabolic response in the sites of primary disease while also revealing new subcutaneous lesions, which were biopsy-proven recurrent disease. This case illustrates the importance of the different biological behavior of MCL, whereby new sites of metabolically active lesions can represent recurrent disease, even though there is a complete metabolic response at sites of primary disease.
Keywords: Fluorodeoxyglucose-positron emission tomography/computed tomography; mantle cell lymphoma; recurrent lymphoma; treatment response